The sun collective eaudiobook A novel. - Baxter, Charles (Random House Audio, 2020)
*A NEW YORK TIMES 2021 NOTABLE BOOK* A timely and unsettling novel about the people drawn to and unmoored by a local activist group more dangerous than it appears—from the winner of the PEN/Malamud Award and “one of our most gifted writers” ( Chicago Tribune ). Once a promising actor, Tim Brettigan has gone missing. His father thinks he may have seen him among some homeless people. And though she knows he left on purpose, his mother has been searching for him all over the city. She checks the usual places—churches, storefronts, benches—and stumbles upon a local community group with lofty goals and an enigmatic leader who will alter all of their lives. Christina, a young woman rapidly becoming addicted to a boutique drug that gives her a feeling of blessedness, is inexplicably drawn to the same collective by a man who’s convinced he may start a revolution. As the lives of these four characters intertwine, a story of guilt, anxiety, and feverish hope unfolds in the city of Minneapolis.   A vision of modern American society and the specters of the consumerism, fanaticism, and fear that haunt it, The Sun Collective captures both the mystery and the violence that punctuate our daily lives.